PELAKSANAAN PEMBEBASAN BERSYARAT DI DALAM SISTEM PEMASYARAKATAN SEBAGAI UPAYA INTEGRASI SOSIAL NARAPIDANA (STUDI DI BALAI PEMASYRAKATAN KLAS II PEKANBARU) - Altria Dewi P; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The correctional institution class II in Pekanbaru have duty such as executor, counseling, and supervising of prisoner who got the conditional exemption furthermore, the prisoner will be as client of citizen that will be counselor. In pratice, counseling and surviving client of citizen needs more researches about citizen that have as guide purpose in order to client of citizen will be stand alone and intergration for people. Client of citizen must be report in each month until their sffliction time finishes to the citizen counseling correctional institute class II Pekanbaru. But, in fact most of the prisioner did not their report in each month until two month and three times did not report. The purpose of this research are: first the executor of the conditional exemption in citizen as intergration way and sosialization of prisoner in the correctional institute class II Pekanbaru, the second obstacle in executor of the conditional exemption in citizen system as integration way socialization prisoner in the correctional institute class II Pekanbaru, the third, the way of executor the conditional exemption in the correctional institute class II Pekanbaru.This type of research can be classified in this type of juridical sociological research, because in this study the authors directly conduct research on the location or place diteliiti to provide a complete and clear picture of the problems examined. This research was conducted in the jurisdiction of Balai Pemasyarakatan Klas II Pekanbaru, while the population and sample an entire party is related to the problems examined in this study, which used data sources, primary data and secondary data consisting of primary legal materials, secondary and tertiary, technical data collection in this study with questionnaires, interviews and literature study.From the research, there are three main problems that can be inferred. First, the counseling citizen in executor, counseling, and supervising client of citizen there was no satisfactory. Second, the obstacle that the counseling citizen faced do their job from the justice and about media or tools. Third, the effort that made to know some obstacle from counseling citizen and try in law enforcement and media or tools factors. Advice Author, First law enforcement must increasing their quality and quantity. Second, provide account about money, socialization and diklat about how to increase their duty and job in counseling people. Third, applyin and supply to increase the media and tools in do their job.